Poeta Antônio Apolinário da Cruz: traços biográficos e temáticos na literatura de cordel - Souza, Ana Cleide Patricio de (2022)
The research addressed the Thematic Representation of Information in the pamphlets of the poet Antônio Apolinário da Cruz, the objective of analyzing the trajectory and the themes present in the pamphlets of the author's Cordel Literature. The methodological course consisted of a descriptive research, with a qualitative approach, of a bibliographic and documentary nature. The operationalization of the research took place in stages: in the first stage, we collected the data, through an online search in the catalogs of institutions that contain a collection of Cordel Literature, later we mapped and listed the literary production of the poet Antônio Apolinário da Cruz in these institutions. In the second stage, we adopted content cnalysis to systematize the selected leaflets and analyzed the data based on Bardin (2016) categorization and on Albuquerque (2011) "Thematic Classes", since both corroborate the identification of the themes that make up the the trajectory and work of the poet. We selected thirtythree leaflets to form the corpus. As analysis procedures, we made use of the content of the verses containing elements that deal with themes and trajectory, consulted in the poet's own pamphlets, these being essential informational contributions. We mapped the Brazilian and foreign institutions that preserve the poet's pamphlets in their information units. We identified the themes in the cordel pamphlets of the poet Antônio Apolinário da Cruz; from the content analysis, we verified elements and systematized them in tables and figures for a better organization of the information. From the analysis of the cordel leaflets, the following themes emerged: Accident, Murder, Cure, Corruption, Disaster, Elections, Evangelization, Government, Homage, Death, Power, Politics, Prophecies, Prostitution, Religion, Religiosity, Separation, Temperament and urbanism, with predominance of religiosity, prophecies and power, and as a thematic class: City and Urban Life, Crime, Science, Humor, Weather, Morality, Death, Fight, Power; Political and social, Religion and Health and Diseases. We conclude that the research made it possible to reveal the trajectory of the poet Antônio Apolinário da Cruz and the themes addressed in his cordel booklets.